Anterior Cervical Decompression and Fusion (ACDF) with Titanium Plate and Screw in Rajshahi Medical College Hospital (Medicine Today, 2012)
Medicine Today 2011 Volume 23 Number 01 Page 30-32 DOI: http://dx.doi.org/10.3329/medtoday.v23i1.11942